Using tunable infrared laser direct absorption spectroscopy for ambient hydrogen chloride detection: HCl-TILDAS - J. W. Halfacre; J. Stewart; S. C. Herndon; J. R. Roscioli; C. Dyroff; T. I. Yacovitch; M. Flynn; S. J. Andrews; S. S. Brown; S. S. Brown; P. R. Veres; P. M. Edwards (Atmospheric Measurement Techniques, 2023)
The largest inorganic, gas-phase reservoir of chlorine atoms in the atmosphere is hydrogen chloride (HCl), but challenges in quantitative sampling of this compound cause difficulties for obtaining high-quality, high-frequency measurements. In this work, tunable infrared laser direct absorption spectroscopy (TILDAS) was demonstrated to be a superior optical method for sensitive, in situ detection of HCl at the 2925.89645 cm−1 absorption line using a 3 µm inter-band cascade laser. The instrument has an effective path length of 204 m, 1 Hz precision of 7–8 pptv, and 3σ limit of detection ranging from 21 to 24 pptv. For longer averaging times, the highest precision obtained was 0.5 pptv with a 3σ limit of detection of 1.6 pptv at 2.4 min. HCl-TILDAS was also shown to have high accuracy when compared with a certified gas cylinder, yielding a linear slope within the expected 5 % tolerance of the reported cylinder concentration (slope = 0.964 ± 0.008). The use of heated inlet lines and active chemical passivation greatly improve the instrument response times to changes in HCl mixing ratios, with minimum 90 % response times ranging from 1.2 to 4.4 s depending on inlet flow rate. However, these response times lengthened at relative humidities >50 %, conditions under which HCl concentration standards were found to elicit a significantly lower response (−5.8 %). The addition of high concentrations of gas-phase nitric acid (>3.0 ppbv) were found to increase HCl signal (<10 %), likely due to acid displacement with HCl or particulate chloride adsorbed to inlet surfaces. The equilibrium model ISORROPIA suggested a potential of particulate chloride partitioning into HCl gas within the heated inlet system if allowed to thermally equilibrate, but field results did not demonstrate a clear relationship between particulate chloride and HCl signal obtained with a denuder installed on the inlet.